Educational games, gamification, and teacher roles in supporting primary students’ cognitive development: A systematic literature review (Diniyah: Jurnal Pendidikan Dasar, 2026)
Educational games, gamification, and game-based learning media are increasingly used in primary education to support active learning, engagement, and cognitive development. However, existing studies remain fragmented in terms of media type, learning context, research design, cognitive outcomes, and teacher roles. This study synthesizes empirical evidence on educational games and gamified learning media in elementary school and madrasah ibtidaiyah contexts, focusing on cognitive outcomes, pedagogical implementation, and research gaps. A Systematic Literature Review was conducted following the PRISMA framework. Articles were identified through Publish or Perish, Google Scholar metadata, SINTA, Garuda, and accredited journal websites. From 200 initial records, 13 studies met the eligibility criteria, and 14 additional studies were obtained through targeted searches, resulting in 27 final articles published between 2022 and 2025. Data were analyzed using descriptive quantitative analysis and thematic synthesis based on the PICO framework. Findings show that Wordwall, Quizizz, Kahoot, Genially, PowerPoint-based games, augmented reality, board games, and collaborative game-based learning were commonly used. Reported outcomes included learning achievement, conceptual understanding, literacy, numeracy, problem-solving ability, motivation, engagement, and teacher readiness. The review highlights that game-based learning is most promising when aligned with learning objectives, teacher facilitation, and explicit cognitive assessment. Keywords: educational games; gamification; game-based learning; cognitive development; primary education; systematic literature review